2021
DOI: 10.1007/s00520-021-06414-3
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of peripheral neuropathy in multiple myeloma patients and the impact of vitamin D levels, a cross-sectional study

Abstract: Purpose Peripheral neuropathy (PN) is common in patients with multiple myeloma (MM). We hypothesized that the relationship between hypovitaminosis D and PN described in diabetes mellitus patients may also be present in MM patients. Methods To study this potential association, we assessed the incidence of hypovitaminosis D (vitamin D < 75 nmol/L [= 30 ng/mL]) in smouldering and active MM patients in two Dutch hospitals. Furthermore, a validated questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Records from all three deduped databases were then amalgamated in Zotero and underwent inter-database deduplication, removing 207 studies, leaving 1264 which were subsequently uploaded to Rayyan for screening. Abstract and title screening (blinded) performed independently by two investigators (NM and AP) excluded 1214 records, leaving 50 to screen by full text, of which 35 were subsequently excluded, yielding 15 publications [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] for this scoping review. One study produced two publications reporting on different outcomes [ 21 , 22 ]; hence 14 separate studies were identified yielding 15 overall publications.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Records from all three deduped databases were then amalgamated in Zotero and underwent inter-database deduplication, removing 207 studies, leaving 1264 which were subsequently uploaded to Rayyan for screening. Abstract and title screening (blinded) performed independently by two investigators (NM and AP) excluded 1214 records, leaving 50 to screen by full text, of which 35 were subsequently excluded, yielding 15 publications [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] for this scoping review. One study produced two publications reporting on different outcomes [ 21 , 22 ]; hence 14 separate studies were identified yielding 15 overall publications.…”
Section: Resultsmentioning
confidence: 99%
“…All of the identified studies in this scoping review applied an observational study design, including four cross-sectional studies (yielding five publications) [ 19 , 21 , 22 , 24 , 28 ], three retrospective cohorts [ 14 , 17 , 27 ], two case-control studies [ 16 , 25 ], one cross-sectional study with an additional retrospective chart review [ 18 ], one retrospective chart review [ 26 ], one matched controlled cohort [ 23 ], one prospective cohort [ 20 ], and one case report [ 15 ]. No experimental studies were identified in the literature landscape.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations